Use of Spring Whistle Counts to Predict Northern Bobwhite Relative Abundance - D. Clay Sisson; Theron M. Terhune II (National Quail Symposium Proceedings, 2017)
Spring whistle counts are commonly used to index northern bobwhite (Colinus virginianus) breeding populations and make inference about relative autumn abundance. They are relatively cheap and easy to implement and provide the advantage of surveying bobwhite populations from multiple points daily and early in the year. This could prove useful on properties available for potential lease, purchase, or as translocation sites; as well as to monitor population trends. Our objective was to determine whether spring whistle counts reliably forecast autumn covey numbers on a wide range of sites, years, and densities on 6 properties in southwestern Georgia from 2006 to 2015. We conducted spring whistle counts weekly during peak calling activity (late May–early Jun, for 4–6 consecutive years) on an average of 7 points/property (range = 5–9). We conducted autumn covey counts using these same sampling points as an index of relative abundance. Peak number of males heard in spring and number of coveys heard in autumn was strongly correlated (R2 = 0.791, n = 198) for all points combined, indicating that spring whistle counts are a reliable tool for assessing bobwhite relative abundance on sites where autumn covey counts are precluded or the information is needed prior to autumn.
Keywords: northern bobwhite; colinus virginianus; covey counts; Georgia; translocation; whistle counts